Komunikasi sebagai Wacana - Ibnu Hamad (MediaTor (Jurnal Komunikasi), 2006)
The purpose of this article is to describe communication as discourse perspective. In this perspective communication is seen an activity to construct of reality into a discourse that some interests entering the discourse. The perspective is to complete to the others ones, first transmissions perspective. Communication is to transmit of messages linearly. Second, perspective of display. Communication is an effort to exhibit many messages for gaining audiences attention. Third, generating of meaning perspective where we use symbols to create meaning. Fourth, ritual perspective which communication as a rites to maintain commonness and solidarity of the participants.